Kampanye Public Relations Program Bandung Tanginas Untuk Menekan Angka Stunting - Husin, Muhammad Husin; Mukarom, Zaenal (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
Public Relations Campaign is a planned communication activity within a certain period of time, which aims to provide knowledge and influence the target audience, as well as to create trust and a good impression of the public towards the institution, company or organization that organizes the activity. The purpose of this study was to determine the Public Relations of the Bandung City Health Office in carrying out the pre-campaign stages, planning stages, implementation stages, and post-campaign stages to reduce stunting rates in the city of Bandung. The results of this study illustrate that the public relations campaign strategy used by the Public Relations of the Bandung City Health Office in an effort to reduce stunting rates in the city of Bandung is by 1) identifying problems, 2) collaborating with various sectors, 3) determining the objectives of the campaign implementers, 4) determining target audiences and campaign messages, 5) formulating campaign approaches and channels, 6) packaging campaign messages, 7) direct campaigns, 8) campaigns through the media, 9) monitoring and evaluation, 10) viewing direct campaign responses, 11) viewing campaign responses through the media.